Reliable and rapid characterization of functional FCN2 gene variants reveals diverse geographical patterns - Ojurongbe Olusola; Ouf Eman; Van Tong Hoang; Toan Nguyen L; Song Le H; Luz Paola R; Messias-Reason Iara JT; Nurjadi Dennis; Zanger Philipp; Kun Jürgen FJ; Kremsner Peter G; Velavan Thirumalaisamy P (BMC, 2012)
Abstract Background Ficolin-2 coded by FCN2 gene is a soluble serum protein and an innate immune recognition element of the complement system. FCN2 gene polymorphisms reveal distinct geographical patterns and are documented to alter serum ficolin levels and modulate disease susceptibility. Methods We employed a real-time PCR based on Fluorescence Resonance Energy Transfer (FRET) method to genotype four functional SNPs including -986 G > A (#rs3124952), -602 G > A (#rs3124953), -4A > G (#rs17514136) and +6424 G > T (#rs7851696) in the ficolin-2 (FCN2) gene. We characterized the FCN2 variants in individuals representing Brazilian (n = 176), Nigerian (n = 180), Vietnamese (n = 172) and European Caucasian ethnicity (n = 165). Results We observed that the genotype distribution of three functional SNP variants (−986 G > A, -602 G > A and -4A > G) differ significantly between the populations investigated (p < 0.0001). The SNP variants were highly linked to each other and revealed significant population patterns. Also the distribution of haplotypes revealed distinct geographical patterns (p < 0.0001). Conclusions The observed distribution of the FCN2 functional SNP variants may likely contribute to altered serum ficolin levels and this may depend on the different disease settings in world populations. To conclude, the use of FRET based real-time PCR especially for FCN2 gene will benefit a larger scientific community who extensively depend on rapid, reliable method for FCN2 genotyping.